Interview with Dr. Rosa Filipchuk de Romero - Chuhue Huamán, Richard (2025)
This interview, conducted in 2018, shares the testimony of the remembered philologist Rosa Filipchuk de Romero, former director and founder of the Confucius Institute at the Ricardo Palma University. The interview develops details of the academic training and memories of the prominent Peruvian-Ukrainian professional, as well as recounts aspects of the development and progress of the University. The dialogue runs in an entertaining manner while various themes of personal history intertwined with world events in the 20th century are revealed. Dr. Filipchuk’s posthumous testimony outlines the importance of her career and leaves us with a heartfelt message of how it should serve as an example for the entire university community.